2021
DOI: 10.3892/mmr.2021.12029
|View full text |Cite
|
Sign up to set email alerts
|

ASMq protects against early burn wound progression in rats by alleviating oxidative stress and secondary mitochondria‑associated apoptosis via the Erk/p90RSK/Bad pathway

Abstract: Burn wounds present an evolutionary progression, in which the initial wound tissue deepens and expands following thermal injury. Progressive tissue damage in the zone of stasis may worsen burn injury, which is associated with oxidative stress and secondary apoptosis, and worsen the prognosis of patients with burn wounds. The mitochondrial apoptotic pathway is involved in receiving oxidative signals and regulating tissue apoptosis. Previously, Abnormal Savda Munziq (ASMq), a natural compound of traditional Uygh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the laboratory, Zhou et al, using a rat model, discovered, after the application of nanofat to burn wounds not only healed faster due to increased rates of cell proliferation but also formed more new micro vessels due to the upregulation of vascular endothelial growth factor production. 32 Clinically, Rigotti et al demonstrated the histological effects of ASCs on aged facial skin. 18 …”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory, Zhou et al, using a rat model, discovered, after the application of nanofat to burn wounds not only healed faster due to increased rates of cell proliferation but also formed more new micro vessels due to the upregulation of vascular endothelial growth factor production. 32 Clinically, Rigotti et al demonstrated the histological effects of ASCs on aged facial skin. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The unphosphorylated form of Bad, a Bcl‐2 family member, can bind to Bcl‐xL or Bcl‐2 and inhibit their anti‐apoptotic potential, enhancing cytochrome C release and caspase activation (Cook et al, 2017; Danial, 2008; Kheirallah et al, 2013). Several studies have shown that the ERK1/2‐P90RSK‐Bad pathway may protect against apoptosis (Fang et al, 2019; Park et al, 2018; Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These re show that cinnamon aqueous extract, acting on the transcription factors NF-KB and 1, has an important anti-cancer effect in vivo [1]. Even if aqueous cinnamon extrac not lead to morphological changes in cells 24 h from exposure, a progressive augme apoptotic cells has been observed [18] and it seems that the apoptosis rate gradual creases depending on the time from cinnamon administration; in fact, in order to v this condition, neoplastic cells of colorectal adenocarcinoma have been treated with natural compound and showed a similar time-related pattern in increasing apoptosis Furthermore, aqueous cinnamon extract proved to be capable of stimulating the ex sion of pro-apoptotic genes such as Bim and Bax [19][20][21][22][23][24][25][26].…”
Section: Inhibition Of Nf-kb and Ap-1mentioning
confidence: 99%